Functional groups in phytoecology: an application to the study of isolated plant communities in Mediterranean France - Médail, F; Roche, Philip; Tatoni, Thierry (Acta Oecologica, 1998)
e main objective of this study is to compare functional patterns versus plant composition in holm-oak forest isolates from two sites of Provence (Mediterranean France), on siliceous (Maures) or calcareous substrates (Luberon). In order to define plant functional groups, 9 traits out of a total of 71 attributes, were used. Twenty functional groups were defined with predominantly vegetative traits. Within each site, edges and forested core areas refer to different functional groups, in relation to the isolate structure and disturbance effects. In siliceous Provence, a higher structural and functional diversity occurs inside isolates, whereas on calcareous substrate, the diversity of plant functional groups which charac- terizes edges, is as important as in internal parts of isolates. Functional diversity does not necessarily follow the same patterns as the specific diversity, which is always greater in edges. Thus, the use of some sets of attributes, resulting from evolutionary trade-off between plants and their environment, can provide a better understanding of ecological consequences of disturbances. 0
Keywords: biological conservation; disturbances; ecosystems; fragmentation; functional diversity; Functional groups; Mediterranean-type ecosystems; terrestrial islands